A novel methodology for the extraction, purification and characterization of immunoglobulin G (IgG) nanoparticles from bovine colostrum: implications for food and therapeutic industries - Fawze Alnadari; Yusof A.Y.A. Mohammed; Mustapha Muhammad Nasiru; Amirah S. Alahmari; Mohammed A. Alqahtani; Osama Abdulaziz; Isaiah Henry Ibeogu; Rongchang Wang; Chao Chen; Salem Baldi; Ibrahim Khalifa; Mohamed Abdin; et al. (Results in Engineering)
Immunoglobulin G (IgG) derived from bovine colostrum (BC) is essential for immune defense systems and holds significant potential in pharmaceuticals, food preservation, and therapeutics. However, its susceptibility to environmental stressors, such as heat and enzymatic degradation, has limited its practical use. This study introduces a novel, eco-friendly method for synthesizing IgG nanoparticles (IgG NPs) from BC, leveraging a self-assembly approach without toxic chemical agents. The resulting IgG NPs exhibited a significantly higher IgG concentration (80.1 %) compared to polymeric IgG (69 %) and BC after fat removal (35 %), as confirmed by HPLC and SDS-PAGE analyses. Characterization via Transmission electron microscopy (TEM) and Scanning electron microscopy (SEM) revealed that IgG NPs possess a uniform spherical morphology with a size range of 20–200 nm, demonstrating superior thermal stability and reduced crystallinity relative to polymeric IgG. Remarkably, IgG NPs retained their structural integrity and bioactivity even after prolonged exposure to 85 °C for 60 min, while polymeric IgG suffered extensive degradation, aggregation, and precipitation under the same conditions. Amino acid profiling further underscored the stability of IgG NPs, which maintained higher concentrations of essential amino acids (e.g., Phenylalanine, Leucine, and Valine) over time, whereas polymeric IgG exhibited significant losses. FT-IR and XRD analyses confirmed that the chemical structure of IgG remained intact during nanoparticle formation, preserving its native functionality. Thermogravimetric analysis (TGA) revealed that IgG NPs had enhanced thermal resistance, with minimal weight loss up to 440 °C. Rocket immunoelectrophoretic demonstrated that IgG NPs retained consistent antigen-antibody interactions across varying concentrations, highlighting their potential for diagnostic and therapeutic applications. These findings position IgG NPs as a groundbreaking alternative for biomedical and pharmaceutical applications, offering enhanced stability, biocompatibility, and cost-effectiveness. Future research could explore their use in targeted drug delivery, immunomodulation, and functional food formulations, paving the way for innovative solutions in healthcare and biotechnology.